# 1)How can we correct the sentence:

• 22-Aug-2008, 15:19
belly_ttt
1)How can we correct the sentence:
1)How can we correct the sentence:
When the eggs hatch, the young turtles go off to take care of themselves, being that female turtles do not nurture their young
a) add "on the other hand" at the beginning
b) insert " as a result" at the bginning"
c) change the comma to semicolon
d) change "hatch" to "hatched"
e) change "being that"-> "because"

The answer was e. But I have never seen a "because" after comma

2) The meaning of his words was even more elusive in his own country than either Europe or Latin America ( the underscore is a wrong phrase)
Can we replace the underscored phrase with "either in Europe or Latin Am" or " in either Europe or Latin Am"?

3) On my preparing for exam, I came up with this sentence:
Spot the error:
Kelly is proud of her own abilities to mediate disputes more than any of her other strength. No error

The answer was C ( as the book says) but here is its explanation:
"Does the subordinate clause fit within the context of the sentenc? ( A) uses the correct verb tense and the verb agrees w/ subject Kelly. (B) shows the correct feminine sing. pronoun, referring to Kelly (C) shows the correct infi. form of the verb mediate.

4) here is part of a math question I couldn't find out why:
Which is the graph of y= -(x-2)2 (2 outside the bracket means square)?

Graphs drawn below.

And here was the solution:
If f(x) = -x2 , the given equation, y= -(x-2)2, represents f(x-2)

How come they got the last line?
• 23-Aug-2008, 06:41
Raymott
Re: 1)How can we correct the sentence:
Quote:

Originally Posted by belly_ttt
4) here is part of a math question I couldn't find out why:
Which is the graph of y= -(x-2)2 (2 outside the bracket means square)?

Graphs drawn below.

And here was the solution:
If f(x) = -x2 , the given equation, y= -(x-2)2, represents f(x-2)
How come they got the last line?

I'll explain the Maths one. (You can use a ^ to signify 'to the power of')
Let x = 5 (for illustration. x will remain 5 for the whole exercise)
f(x) = - x^2
f(x) is a function which takes any value (x), squares it, then negates it.
So, if x = 5, f(5) = - x^2 = -25
In this case, x-2 is 5-2 = 3, so f(3) = -9
So f(x-2) = -9
And y = -(x-2)^2 = - (5-2)^2 = -(3)^2 = -9
So f(x-2) = y = -(x-2)^2

But put simpler, you can substitute anything for x
If you change f(x) to f(x-2), then - x ^2 becomes - (x-2)^2, which is y.
And it even works without colours! :-D

Search Engine Optimization by vBSEO 3.6.1